2006
DOI: 10.1590/s1677-55382006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Salvage conformal radiotherapy for biochemical recurrent prostate cancer after radical prostatectomy

Abstract: Objective: Assess the results of salvage conformal radiotherapy in patients with biochemical failure after radical prostatectomy and identify prognostic factors for biochemical recurrence and toxicity of the treatment. Materials and Methods: From June 1998 to November 2001, 35 patients were submitted to conformal radiotherapy for PSA ≥ 0.2 ng/mL in progression after radical prostatectomy and were retrospectively analyzed. The mean dose of radiation in prostatic bed was of 77.4 Gy (68-81). Variables related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…In this meta-analysis, eight studies evaluated the surgical margins910131416171920 However, the overall effect showed no significant association between surgical margins and BCR (OR: 1.09; 95% CI: 0.83–1.43). The fixed-effects model was reported here because there was no evidence of heterogeneity ( I 2 = 30%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…In this meta-analysis, eight studies evaluated the surgical margins910131416171920 However, the overall effect showed no significant association between surgical margins and BCR (OR: 1.09; 95% CI: 0.83–1.43). The fixed-effects model was reported here because there was no evidence of heterogeneity ( I 2 = 30%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 86%
“…Of these 204 papers, 196 were finally excluded because they did not meet the inclusion criteria. In addition, four papers were identified from the reference lists 13141516. Finally, a total of 11 papers were eligible for review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A low pretreatment PSA level is an important factor for sRT to be successful. The borderline value of PSA for excellent results of sRT is 1.5 and 2.0 ng/ml, respectively [29][30][31][32][33][34][35][36][37] . Other prognostic factors for the efficacy of sRT are: PSADT [38][39][40][41][42] , PSA before RP [22,23] , seminal vesicle invasion [23,24,27,43,44] and extracapsular extension [27,43,44] .…”
Section: Discussionmentioning
confidence: 99%